JUVENILE-ONSET SYSTEMIC LUPUS ERYTHEMATOSUS: CLINICAL FEATURES AND CURRENT DIAGNOSTIC APPROACHES - M. I. Kaleda; I. P. Nikishina (Научно-практическая ревматология, 2017)
Systemic lupus erythematosus (SLE) is an autoimmune disease with various organs and systems involved in the pathological process, with an unpredictable course, a risk for life-threatening conditions, and an onset from childhood through adolescence in 10–20% of cases. The onset of SLE prior to adult age affects its clinical manifestations, course, and prognosis. Based on the data available in the literature, the paper analyzes the features of the onset and clinical presentations of SLE in children and adolescents and discusses the aspects of verifying its diagnosis, by taking into account the need to use early effective personalized therapy and to improve prognosis.